The effect of continuum beliefs on public stigma of depression with evidence from explicit and implicit sources - Xuanyi Wang; Qiuyu Lv; Minghui Lu; Weiguo Qu (Scientific Reports)
Abstract Stigmatization of depression serves as a significant barrier to both treatment-seeking behaviors and recovery outcomes. While the Continuum Beliefs Approach (CBA) has shown promise in reducing explicit stigma, its impact on implicit attitudes remains unclear. Participants were randomly assigned to continuum beliefs, categorical beliefs, or control groups. Explicit stigma was measured through questionnaires (n = 323) and implicit stigma were assessed using the Single Category Implicit Association Test (n = 252). Results revealed that the continuum beliefs group exhibited significantly lower explicit stigma across cognitive (negative stereotypes), affective (prejudicial affective reactions), and behavioral (social distance acceptance) dimensions. However, no between-group differences emerged for implicit stigma, with participants across all groups demonstrating significant implicit stigma toward depression. While continuum belief interventions effectively reduce explicit stigma, they appear insufficient to modify the deeply ingrained automatic biases that constitute implicit stigma toward depression. These findings highlight the complexity of stigma reduction efforts and the limitations of brief interventions in modifying implicit stigma towards depression.